Reading Emotions from Body Movement: A Generalized Impairment in Schizophrenia - Vaskinn, Anja; Sundet, Kjetil; Østefjells, Tiril; Nymo, Katharina; Melle, Ingrid; Ueland, Torill (Frontiers in Psychology, 2016)
Body language reading is a social cognitive process with importance for successful maneuvering of social situations. In this study, we investigated body language reading as assessed with human point-light displays in participants with a diagnosis of schizophrenia (n = 84) compared to healthy control participants (n = 84), aiming to answer three questions: 1) whether persons with a diagnosis of schizophrenia have poorer body language reading abilities than healthy persons; 2) whether some emotions are easier to read from body language than others, and if this is the same for individuals with schizophrenia and healthy individuals, and 3) whether there are sex differences in body language reading in participants with schizophrenia and healthy participants. A fourth research aim concerned associations of body language reading with symptoms and functioning in participants with schizophrenia. Scores on the body language reading measure was first standardized using a separate sample of healthy control participants (n = 101). Further results showed that persons with schizophrenia had impaired body language reading ability compared to healthy persons. A significant effect of emotion indicated that some emotions (happiness, neutral) were easier to recognize and this was so for both individuals with schizophrenia and healthy individuals. There were no sex differences for either diagnostic group. Body language reading ability was not associated with symptoms or functioning. In conclusion; schizophrenia was characterized by a global impairment in body language reading that was present for all emotions and across sex.